Faktor Kunci Kepatuhan Pajak UMKM E-Commerce di DKI Jakarta : Modernisasi Sistem Pajak, Religiusitas, Love of Money, dan Sanksi Pajak - Alfi, Muhammad Khoirul; Wijaya , Suparna (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to examine how Religiosity, love of money, tax sanctions, and modernization of the tax system affect tax compliance of MSME businesses. Methodology: The sampling method is based on the formula of Roscoe's theory. Using the SmartPLS 4.0 program for PLS-SEM data analysis, the researcher tested the hypothesis at a significance level of 5%. Results: the results of the study, taxpayer compliance in e-commerce is significantly influenced by the modernization of the tax system for MSMEs; taxpayer compliance in is not significantly influenced by religiosity for the same business; and e-commerce is significantly influenced by love of money. In terms of MSME e-commerce tax compliance, tax sanctions do not have a significant effect. Limitations: This study may only cover a small portion of e-commerce MSMEs in DKI Jakarta, so the results may not fully represent the entire population of e-commerce MSMEs in the area if the sample used is not taken randomly or there is a tendency to select certain respondents, then the results of the study can be influenced by sample selection bias. Contribution: This study adds to the existing literature on tax compliance, particularly in the context of MSMEs in the e-commerce sector. It provides new insights into how factors such as tax system modernization, religiosity, love of money, and tax sanctions interact to influence tax compliance. By testing a theoretical model involving various factors influencing tax compliance, this study strengthens or challenges existing theories related to tax compliance behavior, particularly in the context of the digital economy